The role of the currency auction in the illicit financial flows in Iraq (Eurasian Journal of History, Geography and Economics, 2022)
Illicit financial flows refer to capital flows that are illegally collected, transferred, or used. Because of these flows, the country is exposed to the loss of its resources in three aspects. The first is the loss of these flows, which can become a source for financing domestic investment and reducing the need for foreign exchange. The second is the loss of revenue flows, and finally, governments’ loss of tax revenues resulting from these flows and their returns.The research attempts to estimate the volume of illegal financial flows in Iraq that pass through the currency auction and then determine the size and importance of the losses exposed to the Iraqi economy because of these flows.